Apoptosis and APC in colorectal tumorigenesis. - Morin, P J (1996)
Tumors result from disruptions in the homeostatic mechanisms that regulate cell birth and cell death. In colon cancer, one of the earliest manifestation of this imbalance is the formation of polyps, caused by somatic and inherited mutations of the adenomatous polyposis coli (APC) tumor suppressor gene in both humans and mice. While the importance of APC in tumorigenesis is well documented, how it functions to prevent tumors remains a mystery. Using a novel inducible expression system, we show that expression of APC in human colorectal cancer cells containing endogenous inactive APC alleles results in a substantial diminution of cell growth. Further evaluation demonstrated that this was due to the induction of cell death through apoptosis. These results suggest that apoptosis plays a role not only in advanced tumors but also at the very earliest stages of neoplasia.